Effect of reversal of deep neuromuscular block with sugammadex or moderate block by neostigmine on shoulder pain in elderly patients undergoing robotic prostatectomy. (February 2020) - Williams, Wendell H.; Cata, Juan P.; Lasala, Javier D.; Navai, Neema; Feng, Lei; Gottumukkala, Vijaya
Abstract: Background: For some laparoscopic procedures, deep neuromuscular block has been shown to facilitate lower insufflation pressures and lower patient pain scores, and enhance postoperative recovery. We investigated the impact of deep neuromuscular block and its reversal on postoperative shoulder pain and outcomes after robotic prostate surgery. Methods: Elderly men undergoing robotic prostatectomy were randomised to deep neuromuscular block (target post-tetanic twitch of 1–2 at the facial nerve) with sugammadex reversal or moderate neuromuscular block (target 1–2 train-of-four ratio) with neostigmine reversal. The primary endpoint was postoperative shoulder pain. The secondary endpoints included intraoperative insufflation pressure, surgical rating score, incidence of residual neuromuscular block, and postoperative recovery. Results: A total of 50 subjects for each treatment arm were included in the analysis. The degree of neuromuscular block had no effect on the incidence of shoulder pain (deep block group 12% vs moderate block group 10%; P =1.0) or average insufflation pressure (median [inter-quartile range]) (13.3 [12.5–13.6] mm Hg vs 13.3 [11.7–14] mm Hg, P =0.86). After surgery, the deep block group had a higher normalised train-of-four ratio (0.98 [0.79–1.11] vs 0.85 [0.74–1.00]; P =0.008). The presence of postoperative shoulder pain was associated with higher BMI (31.8 [28–33.9] kg m −2 vs 28 [24.8–31.1] kg m −2 ; P =0.036) and longer insufflation time (186 [156–257] min vs 154 [126–198] min; P =0.028). Conclusions: The use of deep neuromuscular block during surgery does not decrease postoperative shoulder pain or enhance recovery after robotic prostatectomy. Clinical trial registration: NCT03210376.